Washing or filtering of blood products does not improve outcome in a rat model of trauma and multiple transfusion. Issue 1 (21st November 2018) - Wirtz, Mathijs R.; Jurgens, Jordy; Zuurbier, Coert J.; Roelofs, Joris J.T.H.; Spinella, Philip C.; Muszynski, Jennifer A.; Carel Goslings, J.; Juffermans, Nicole P.
Abstract : BACKGROUND: Transfusion is associated with organ failure and nosocomial infection in trauma patients, which may be mediated by soluble bioactive substances in blood products, including extracellular vesicles (EVs). We hypothesize that removing EVs, by washing or filtering of blood products, reduces organ failure and improves host immune response. MATERIALS AND METHODS: Blood products were prepared from syngeneic rat blood. EVs were removed from RBCs and platelets by washing. Plasma was filtered through a 0.22‐μm filter. Rats were traumatized by crush injury to the intestines and liver, and a femur was fractured. Rats were hemorrhaged until a mean arterial pressure of 40 mm Hg and randomized to receive resuscitation with standard or washed/filtered blood products, in a 1:1:1 ratio. Sham controls were not resuscitated. Ex vivo whole blood stimulation tests were performed and histopathology was done. RESULTS: Washing of blood products improved quality metrics compared to standard products. Also, EV levels reduced by 12% to 77%. The coagulation status, as assessed by thromboelastometry, was deranged in both groups and normalized during transfusion, without significant differences. Use of washed/filtered products did not reduce organ failure, as assessed by histopathologic score and biochemical measurements. Immune response ex vivo was decreased following transfusion compared to sham but did not differ between transfusion groups. CONCLUSION: Filtering or washing of blood products improved biochemical properties and reduced EV counts, while maintaining coagulation abilities. However, in this trauma and transfusion model, the use of optimized blood components did not attenuate organ injury or immune suppression.